2023
DOI: 10.1002/jum.16181
|View full text |Cite
|
Sign up to set email alerts
|

High Intensity Focused Ultrasound Ablation for Patients With Locally Advanced Pancreatic Adenocarcinoma: A Propensity Score‐Matching Analysis

Abstract: Objectives-This retrospective study was conducted to assess the efficacy and safety of high intensity focused ultrasound (HIFU) in combination with chemotherapy compared with chemotherapy alone in treating patients with unresectable locally advanced pancreatic cancer (LAPC).Methods-The data of unresectable LAPC patients who received chemotherapy with or without HIFU ablation were retrieved retrospectively. The overall survival (OS), objective response rate (ORR), cancer antigen 19-9 response rate, and safety w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…High-intensity focused ultrasound (HIFU), radiofrequency ablation (RFA), and microwave ablation (MWA) are the most frequently used thermal ablation techniques in clinics. [11][12][13] Many studies have demonstrated that MBs can accelerate HIFU-induced temperature increases, enlarge the ablation region, and distort and shift the ablation position. 9,14 However, conflicting results regarding the effects of MBs on RFA have been reported.…”
mentioning
confidence: 99%
“…High-intensity focused ultrasound (HIFU), radiofrequency ablation (RFA), and microwave ablation (MWA) are the most frequently used thermal ablation techniques in clinics. [11][12][13] Many studies have demonstrated that MBs can accelerate HIFU-induced temperature increases, enlarge the ablation region, and distort and shift the ablation position. 9,14 However, conflicting results regarding the effects of MBs on RFA have been reported.…”
mentioning
confidence: 99%